Optimasi Tween 80 dan PEG 400 dalam Sediaan Nanoemulgel Minyak Argan (Argania Spinosa (L.) Skeels) dan Uji Antioksidan Menggunakan Metode DPPH - Jingga Prasasti Sanglyazzahra; Erindyah R. Wikantyasning (Journal of Pharmaceutical and Sciences, 2026)
This study aims to optimize the concentrations of Tween 80 and PEG 400 in the formulation of argan oil nanoemulgel and to evaluate its antioxidant activity using the DPPH method. The nanoemulsion optimization process was carried out using the Simplex Lattice Design (SLD) approach, employing percent transmittance, pH, and emulsification time as response parameters. The optimal results were obtained at a concentration of 60% Tween 80 and 30% PEG 400, with a desirability value of 0.886. The optimized nanoemulsion exhibited a particle size of 31.3 ± 0.21 nm and a polydispersity index of 0.364, meeting the standard criteria for nanoemulsion systems. The resulting nanoemulgel demonstrated favorable physical characteristics, including homogeneous consistency, a spreadability value of 5.03 ± 0.21 cm, an adhesion time of 2.9 ± 0.41 seconds, a viscosity of 29,780 cPs, and a pH of 6.1 ± 0.07. Antioxidant evaluation showed that the argan oil nanoemulgel exhibited strong activity with an IC50 value of 100.33 µg/mL. These results indicate that the optimized nanoemulgel formulation is capable of maintaining the antioxidant activity of argan oil and has strong potential for development as an effective and stable anti-aging cosmetic product.